The New Middle Ages in the Philosophy of History of Nikolai Berdyaev - Nedeljković, Zoran D. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The author discussed the philosophy of history of Nikolai Berdyaev on the basis of appropriate literature. His understanding of the meaning of history and the new Middle Age is based on philosophy of freedom. History without freedom is void of any meaning. A man realizes his freedom only in the community with the Holy Trinity. The arrival of Christ was the victory of freedom over the kingdom of necessity of a sinful nature. The pagan concept of destiny was expelled from the vocabulary of a free man. In the history of mankind, as a common spiritual basis of the Renaissance and Reformation, Berdyaev sees humanism. In the analysis of the internal nature of humanism, Berdyaev recognizes the man’s rebellion against God. He follows the unity of man and god through the Renaissance, whose end extends beyond its temporal boundaries in futurism and cubism of the twentieth century. The philosopher of freedom points out that humanism, paradoxically, turned completely against mankind. In order to illustrate this idea, in the history of art, science, and philosophy, he finds examples of the disappearance of man. Berdyaev compared the spiritual state of mankind of the ninety twenties to the epoch of the Roman emperor Diocletian, when the mass exile of the Christians began. According to many signs, European society should enter a new historical era similar to the 7th, 8th, and 9th centuries, in the pre-Medieval period. The author believes that the feudalization of Europe, with the weakening of the role of the state and transnational companies in political life, is only formal, insufficient that it can be concluded that we are getting closer to the new Middle Age, because a man through his wanting to be the measure of all things, has diminished himself as a thing.